Pengaruh Pemanfaatan Rod Visual Management System (Rvms) Dan Kompetensi Karyawan Terhadap Efisiensi Kerja Karyawan Pada PT Shimano Batam - tukino tukino (Computer Based Information System Journal, 2014)
The purpose of this research is to (1) the effect of Visual Rod Utilization Management System (RVMS) of the Employee Efficiency in PT Shimano Batam partially; (2) Effect on Employee Competency partially Employee Efficiency; (3) Effect of Utilization Rod Visual Management System (RVMS), and Competencies Employee to Employee efficiency simultaneously. Rod Visual Management System (RVMS) is an information system that is used to present information to support operations, management, and decision-making in an Employee organisasi.Kompetensi a framework that guide everyday behavior in making decisions for employees and directing the actions of employees to achieve organizational goals. Decision-making (decision making) is the process of identifying problems and opportunities and then memecahkannnya. This study includes quantitative. The population in this study were employees of PT Shimano Batam. Research sampling technique using a Likert scale technique. In the research paradigms are thought to influence utilization Rod Visual Management System (RVMS), and Competencies Employee to Employee Efficiency.